THU0117 PERSONS AT RISK OF RHEUMATOID ARTHRITIS OR AXIAL SPONDYLOARTHRITIS HAVE DIFFERENT PERCEPTIONS ON PREVENTIVE INTERVENTION THAN RHEUMATOLOGISTS. (2nd June 2020) - Van Boheemen, L.; Bolt, J. W.; Ter Wee, M.; De Jong, H.; Van de Sande, M.; Van Schaardenburg, D.
Abstract : Background: Persons at risk of developing rheumatoid arthritis (RA) may benefit from lifestyle 1 or pharmacological 2 intervention aimed at primary prevention. Although less studied, the same may apply to persons at increased risk of axial spondyloarthritis (axSpA) 3 . Patients' perceptions and physicians' views of risk and benefit have an important influence on patients' willingness to use treatment as previously shown in axSpA. Objectives: Our aim was to investigate and compare the willingness of individuals at-risk of RA or axSpA and rheumatologists to initiate preventive intervention. Methods: Individuals at risk of RA, defined as arthralgia and anti-citrullinated protein antibodies (ACPA; >10 kU/l) and / or rheumatoid factor (RF; >5 kU/l) without arthritis (Reade pre-RA cohort; n=100), healthy first degree relatives (FDR) of HLA-B27 positive axSpA patients (Amsterdam UMC pre-SpA cohort; n=38) and Dutch rheumatologists (n=49) completed a survey on preventive intervention in the at risk phase of RA (pre-RA cohort and rheumatologists) or axSpA (Pre-SpA cohort). The survey included questions on lifestyle intervention, disease perception and scenarios varying in disease risk, treatment effectiveness and side effects of hypothetical preventive medication 4 . Results: Overall participants depicted RA and axSpA to be a serious disease (RA: median VAS (0-10) 6.5, IQR 5-8; SpA: median VAS 6, IQR 4-8). Despite some concern about their increased risk, most persons did not expect to develop the disease (both: median VAS 3, IQR 1-5). Persons who considered RA to be a serious disease were more likely to start preventive intervention (OR 1.14, 95%CI 1.00;1.31). 100% of at risk patients were willing to change at least 1 of 13 lifestyle components: i.e. smoking, alcohol consumption, exercise and diet and in total a medium number of 7 (pre-RA: IQR 4-10, pre-SpA: IQR 5-8) while 35% of rheumatologists gave lifestyle advice to ≥50% of at risk patients (most often smoking cessation). At 30% disease risk, the willingness to use 100% effective preventive medication with no side effects was 53% (pre-RA), 55% (pre-SpA) and 74% (rheumatologists) which increased at 70% disease risk to 69% (pre-RA) and 92% (pre-SpA and rheumatologists). At 30% disease risk and minor side effects, willingness was 26% in pre-RA, 29% in pre-SpA and 31% by rheumatologists and at 70% disease risk 40%, 66% and 76% for pre-RA, pre-Spa and rheumatologists respectively. Differences between rheumatologists and persons at risk are shown in table 1 . Of the rheumatologists 16% indicated that a 30% RA risk in 3 years was needed to start preventive therapy and another 16% preferred a 70% risk before starting medication. Conclusion: Disease risk perception and willingness to start preventive intervention were comparable between pre-SpA and pre-RA patients. They seem willing to make several lifestyle changes to decrease disease risk and were generally willing to use medication in case of a clearly increased risk. Rheumatologists were overall more likely than at risk individuals to start preventive medication. Lifestyle advice was given less frequently by rheumatologists contrasting with individuals' high willingness to adjust lifestyle. References: [1]Zaccardelli A et al. Clin Ther. 2019;41(7):1323-45 [2]Cope AP et al. Clin Ther. 2019;41(7):1299-311 [3]Brown MA et al. Ann Rheum Dis. 2000;59(11):883-6 [4]de Winter et al. Clin Rheumatol. 2019 Mar;38(3):755-759 Disclosure of Interests: Laurette van Boheemen: None declared, J.W. Bolt: None declared, Marieke ter Wee: None declared, Henriëtte de Jong: None declared, Marleen van de Sande Grant/research support from: Novartis, Eli Lilly, Boehringer Ingelheim, Janssen, Consultant of: Abbvie, Novartis, Eli Lilly, Speakers bureau: Novartis, MSD, Dirkjan van Schaardenburg: None declared